Analisis Maqāṣid al-Syarī’ah terhadap implementasi Bantuan Sosial (Bansos) Pangan terhadap Kesejahteraan Multidimensi di Indonesia (2020-2023) - Risdayani, Risdayani; Isman, Isman; Hidayat, Syamsul; Yanuri, Yusuf Rohmat (AL-IKTISAB: Journal of Islamic Economic Law, 2024)
This research project aims to analyze the effectiveness of food social assistance regulations in Indonesia on multidimensional welfare from the perspective of maqāṣid al-syarī’ah. This research employs a mixed-methods approach, integrating both quantitative and qualitative techniques. The quantitative methods include linear regression tests, while the qualitative methods comprise qualitative descriptive analysis. The findings of this research indicate that the food social assistance program, implemented from 2020 to 2023, had a negligible impact on multidimensional welfare indicators in Indonesia, including the unemployment rate, poverty, and the human development index. While the relationship between food social assistance and the Human Development Index (HDI) is relatively weak, there are indications that adequate food access can improve people's nutrition and health. When viewed through the lens of maqāṣid al-syarī’ah, which prioritizes the pursuit of beneficial outcomes, the implementation of food social assistance aligns with the principles of maqāṣid al-syarī’ah, namely the preservation of religion (hifdz al-dīn), the preservation of the soul (hifdz al-nafs), the preservation of reason (hifdz al-’aql), the preservation of property (hifdz al-māl), and the preservation of offspring (hifdz al-nasl). It is hoped that this research will provide guidance for the government in improving food social assistance and other policies for the benefit of the community in line with maqāṣid al-syarī’ah.